Factors Associated with Malocclusion in Preschool Children in a Brazilian Small Town - Assis, Wagner Couto (2022)
Objective: To analyze the prevalence and factors associated with malocclusions in preschool children. Material and Methods: A census, epidemiological study, with a cross-sectional, descriptive and analytic sample, was carried out with children aged between 4 and 6 years, matriculated in preschools in the town of Aiquara, Bahia, Brazil. Malocclusion in the deciduous dentition was determined through the application of the index proposed by WHO, with the Foster and Hamilton criteria also being incorporated. The data was tabulated in duplicate in a Microsoft Excel spreadsheet and following correction, was analyzed using the SPSS, STATA and PAST Software. In order to identify the associated factors, we opted for Multiple Poisson regression analysis and Principal Component Analysis (PCA). Results: A total of 148 children were examined and the general prevalence of malocclusions was 69.59%, with 57.5% in the group of 4-year-old, 76.92% those aged 5 years old and 72.46% among children aged 6 years old. In terms of primary canines, 66.2% were identified as class I, 25.7% as class II and 8.1% as class III. Normal overjet was 41.2%, increased overjet 34.5%, edge to edge bite 17.6% and anterior crossbite 6.8%. The normal overbite 51.4%, reduced 20.9% and deep 8.1%. Of the individuals, 20.9% had posterior crossbite. In the Poisson regression analysis and PCA, a statistical association between the malocclusions and dental caries, duration of use of pacifiers, onychophagia and thumb sucking, was identified. Conclusion: The prevalence of malocclusion in preschool children in the small town of Aiquara is high and the associated factors identified are capable of control and prevention.